Simultaneous biodegradation of bifenthrin and chlorpyrifos by Pseudomonas sp. CB2. Issue 5 (4th May 2018) - Zhang, Qun; Li, Shuhuai; Ma, Chen; Wu, Nancun; Li, Chunli; Yang, Xinfeng
ABSTRACT: The degradation of bifenthrin (BF) and chlorpyrifos (CP), either together or individually, by a bacterial strain (CB2) isolated from activated sludge was investigated. Strain CB2 was identified as belonging to genus Pseudomonas based on the morphological, physiological, and biochemical characteristics and a homological analysis of the 16S rDNA sequence. Strain CB2 has the potential to degrade BF and CP, either individually or in a mixture. The optimum conditions for mixture degradation were as follows: OD600nm = 0.5; incubation temperature = 30°C; pH = 7.0; BF-CP mixture (10 mg L −1 of each). Under these optimal conditions, the degradation rate constants (and half-lives) were 0.4308 d −1 (1.61 d) and 0.3377 d −1 (2.05 d) for individual BF and CP samples, respectively, and 0.3463 d −1 (2.00 d) and 0.2931 d −1 (2.36 d) for the BF-CP mixture. Major metabolites of BF and CP were 2-methyl-3-biphenylyl methanol and 3, 5, 6-trichloro-2-pyridinol, respectively. No metabolite bioaccumulation was observed. The ability of CB2 to efficiently degrade BF and CP, particularly in a mixture, may be useful in bioremediation efforts.